2010
DOI: 10.1002/jor.21146
|View full text |Cite
|
Sign up to set email alerts
|

The effects of scapular taping on electromyographic muscle activity and proprioception feedback in healthy shoulders

Abstract: ABSTRACT:We investigated the effects of scapular tape on the electromyographic (EMG) activity of the upper trapezius (UT), lower trapezius (LT), serratus anterior (SA), anterior deltoid (AD), and shoulder proprioception in 12 healthy shoulders. Participants were blindfolded and required to complete a target end/mid range position with the hand. They performed six trials under two experimental conditions; no tape and therapeutic tape. EMG activity was measured by surface electrodes, and proprioception was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 22 publications
3
82
2
11
Order By: Relevance
“…Regarding the high-tension strip, the KT generates a mechanical correction which leads to improved proprioception and motor rehabilitation reducing movements that may be considered harmful and may produce an improved positioning of the shoulder girdle (18) . Inhibition of the upper trapezius has been investigated in other studies (19,23,24) and agree with the findings of the present study when related to it. Using the KT transversely on the upper trapezius with and without tension, it was observed that, regardless of the exerted tension, a reduction of upper trapezius activity was observed during a typing task, which is an important clinical factor in the syndrome treatment of the impact since the upper trapezius is one of the most overloaded muscles in patients.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the high-tension strip, the KT generates a mechanical correction which leads to improved proprioception and motor rehabilitation reducing movements that may be considered harmful and may produce an improved positioning of the shoulder girdle (18) . Inhibition of the upper trapezius has been investigated in other studies (19,23,24) and agree with the findings of the present study when related to it. Using the KT transversely on the upper trapezius with and without tension, it was observed that, regardless of the exerted tension, a reduction of upper trapezius activity was observed during a typing task, which is an important clinical factor in the syndrome treatment of the impact since the upper trapezius is one of the most overloaded muscles in patients.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, the application of tape is extensively used. Two types of tape of different elastic properties have been used in shoulder rehabilitation; Rigid [Ackermann et al, 2002, Alexander et al, 2003, Cools et al, 2002, Host, 1995, Kalter et al, Lewis et al, 2005b, McConnell et al, Selkowitz et al, 2007, Smith et al, 2009 and Elastic taping techniques [Bradley et al, 2009, Garcia-Muro et al, 2010, Hsu et al, 2009, Kase, 2003, Kaya et al, 2011, Lin et al, 2011, Thelen et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A number of hypotheses have been put forward to explain the effects of taping; it has been suggested that taping alters muscle force [Host, 1995, Morrissey, 2000, neuromuscular control [Alexander et al, 2008, Lin et al, 2011, Lohrer et al, 1999 and proprioception [Lin et al, 2011, Morrissey, 2000. One of the other proposed theories suggests that taping achieves its effects via a biomechanical realignment of the joints [Bennell et al, 2000, Host, 1995, Lewis et al, 2005a and restrictions to the joint range of motion [Bradley et al, 2009, McConnell et al].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear what direction of change in muscle activity represents a beneficial effect; a decrease may imply KT is having a supporting effect and the muscle is working more efficiently, while an increase could represent a facilitatory effect and enhanced muscle function (Hsu, Chen, Lin, Wang & Shih, 2009). This is likely to be dependent on the specific muscle being assessed, the selected subjects (healthy or injured subjects) and the taping technique.Study of Lin, Hung & Yang (2011) showed significant changes in EMG activity in the scapular muscles with the application of tape in the asymptomatic group. Proprioceptive feedback was also enhanced with taping.…”
Section: Discussionmentioning
confidence: 96%